Recent Advances in the Prodrug Approach to Parkinson's Disease Therapy - Karaman, Donia; Haddad, Fatma; Sawalha, Maryam; Khawaja, Yahya; Najjar, Anas; Karaman, Rafik (Pharmaceutical Research - Recent Advances and Trends Vol. 3, 2024)
Parkinson's disease is a neurodegenerative disorder that progresses aggressively and depletes the central nervous system of dopamine (DA). Dopamine replacement therapy has several issues, such as poor blood-brain barrier penetration and a progressive decline in treatment responsiveness. The primary components of this treatment are the initial prodrug L-dopa (LD) and actual dopamine. This chapter discusses prodrugs produced and generated chemically, such as amide, dimeric amide, carrier-mediated, peptide transport-mediated, cyclic, and enzyme-model prodrugs. The bioavailability of these kinds of prodrugs in animals was studied. A promising ester prodrug has been invented for intranasal delivery. LD methyl ester is currently in phase III clinical studies. Many amide prodrugs have been developed with better stability than ester prodrugs. Amide and dimeric amide prodrugs offer enhanced pharmacokinetics and greater blood-brain barrier (BBB) penetration. Linking LD to carbohydrates is one approach that draws advantages from the brain's glucose transport mechanisms. While there isn't a DA prodrug on the market at present, prodrugs seem to have a bright future in Parkinson's disease treatment. Prodrugs that contain LD ester, for instance, demonstrate promises in the intranasal delivery of LD, facilitating the absorption of therapeutic agents by the brain. Most DA prodrugs delivered by amide, cyclic, peptidyl, or chemical routes demonstrated better pharmacokinetic properties.